A flavanone from Baccharis retusa (Asteraceae) prevents elastase-induced emphysema in mice by regulating NF-κB, oxidative stress and metalloproteinases. Issue 1 (December 2015) - Taguchi, Laura; Pinheiro, Nathalia; Olivo, Clarice; Choqueta-Toledo, Alessandra; Grecco, Simone; Lopes, Fernanda; Caperuto, Luciana; Martins, Mílton; Tiberio, Iolanda; Câmara, Niels; Lago, João; Prado, Carla
Abstract Background Pulmonary emphysema is characterized by irreversible airflow obstruction, inflammation, oxidative stress imbalance and lung remodeling, resulting in reduced lung function and a lower quality of life. Flavonoids are plant compounds with potential anti-inflammatory and antioxidant effects that have been used in folk medicine. Our aim was to determine whether treatment with sakuranetin, a flavonoid extracted from the aerial parts ofBaccharis retusa, interferes with the development of lung emphysema. Methods Intranasal saline or elastase was administered to mice; the animals were then treated with sakuranetin or vehicle 2 h later and again on days 7, 14 and 28. We evaluated lung function and the inflammatory profile in bronchoalveolar lavage fluid (BALF). The lungs were removed to evaluate alveolar enlargement, extracellular matrix fibers and the expression of MMP-9, MMP-12, TIMP-1, 8-iso-PGF-2α and p65-NF-κB in the fixed tissues as well as to evaluate cytokine levels and p65-NF-κB protein expression. Results In the elastase-treated animals, sakuranetin treatment reduced the alveolar enlargement, collagen and elastic fiber deposition and the number of MMP-9- and MMP-12-positive cells but increased TIMP-1 expression. In addition, sakuranetin treatment decreased the inflammation and the levels of TNF-α, IL-1β and M-CSF in the BALF as well as the levels of NF-κB and 8-iso-PGF-2α in the lungs of the elastase-treated animals. However, this treatment did not affect the changes in lung function. Conclusion These data emphasize the importance of oxidative stress and metalloproteinase imbalance in the development of emphysema and suggest that sakuranetin is a potent candidate that should be further investigated as an emphysema treatment. This compound may be useful for counteracting lung remodeling and oxidative stress and thus attenuating the development of emphysema.